Tribocorrosion behavior of β-type Ti-15Zr-based alloys - Correa, D. R.N. [UNESP]; Kuroda, P. A.B. [UNESP]; Grandini, C. R. [UNESP]; Rocha, L. A. [UNESP]; Oliveira, F. G.M. [UNESP]; Alves, A. C.; Toptan, F. (Elsevier, 2016)
Titanium alloys have different biomedical applications, due to their favorable mechanical, electrochemical and biological properties. However, when applied as orthopedical or dental implants, the metallic material is submitted to intense mechanical wear in a corrosive environment. In general, tribocorrosion behavior is disregarded during the development of new titanium alloys, which is focused on better mechanical or biological compatibility. In this paper, the tribocorrosion behavior of novel titanium alloys, Ti-15Zr-7.5Mo and Ti-15Zr-15Mo, for biomedical applications was investigated. Tribocorrosion tests were performed against an alumina sphere, with OCP and COF monitored during sliding. Average total wear volume was calculated by tridimensional images with confocal microscopy. The results indicated that both alloys present tribocorrosion behavior superior to cp-Ti, being abrasion the main wear mechanism. Wear volume analysis showed that the Ti-15Zr-7.5Mo presented the better tribocorrosion properties, besides the higher Young's modulus.
Keywords: Biomaterial; Mechanical properties; Titanium alloys; Tribocorrosion